1994
DOI: 10.1007/bf02751717
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical impact and predisposing factors for neonatal thrombocytopenia

Abstract: Thrombocytopenia is a common hemostatic abnormality in the newborn infant. The early diagnosis of thrombocytopenia and the underlying primary pathology process play an important role in reducing the risk of severe complications and mortality. We performed a 2-year prospective study of 643 neonates admitted to our neonatology unit to determine the frequency, predisposing factors, and clinical impact of thrombocytopenia. Thrombocytopenia developed in 18.2% of the preterm neonates and 0.8% of the term neonates. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 11 publications
5
18
2
1
Order By: Relevance
“…In agreement with prior findings, [8][9][10] presumed, fungal, Gramnegative, and Gram-positive infections all significantly reduced neonatal PLT counts (Table 2b). In our population, both Gram-positive and Gram-negative infections were associated with lowered PLT counts and a roughly 50% risk of concurrent thrombocytopenia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with prior findings, [8][9][10] presumed, fungal, Gramnegative, and Gram-positive infections all significantly reduced neonatal PLT counts (Table 2b). In our population, both Gram-positive and Gram-negative infections were associated with lowered PLT counts and a roughly 50% risk of concurrent thrombocytopenia.…”
Section: Discussionsupporting
confidence: 91%
“…Documented infections were culture proven (positive blood or spinal fluid culture), and effects were examined by ANOVA using CBCs in which a PLT count was made within 1 week (À2 or þ 5 days) of diagnosis. 10 Infants were considered noninfected outside this interval. Infants with NEC were evaluated separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14 Our results also showed significant increase in risk of intubation and need for mechanical ventilation among cases with decrease in umbilical arterial pH (p=0.001) as suggested by Goldaber et al, and Andres et al 3,14 Decrease in umbilical arterial pH was significantly associated with low Apgar score in our study (p=0.002) which was consistent with result of other studies done by Goldaber et al and Vandenberg et al 14,15 The incidence of thrombocytopenia found in case group was 58%. The reported incidence in our study was similar to study done by Oren et al, Gunn et al, Gluck man et al [16][17][18] In our study, out of 11 babies with significant acidosis 1 baby (9%) died. Other studies show varying results.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Oren et al, an association has been documented between PROM and thrombocytopenia which was similar to results in our study. 17 PROM in mother is a cause of early onset neonatal sepsis eventually leading to neonatal thrombocytopenia.…”
Section: Maternal Risk Factorsmentioning
confidence: 99%